Heavy Metals in Marine Surface Sediments of Daya Bay, Southern China: Spatial Distribution, Sources Apportionment, and Ecological Risk Assessment - Wang, Huijuan; Fan, Zhengqiu; Kuang, Zexing; Yuan, Yuan; Liu, Huaxue; Huang, Honghui (Frontiers in Environmental Science, 2021)
In Daya bay, especially the northwestern region, the natural reserve with larva economic fish and shrimp is not a pure marine any more due to recently increasing anthropogenic activities. This study seasonally collected surface sediments samples from 20 sites of the northwestern Daya bay to evaluate pollution and ecological risks, and to identify possible sources and transport pathways of heavy metals (Cd, Pb, Cr, Cu, Zn, Hg, As). The results showed all concentrations met the primary standard criteria, except for concentrations of Cr in spring and Cu & Zn in autumn in several sampling stations, which the excess rates were 35%, 4.76% and 4.76%, respectively. The geoaccumulation index （Igeo）values of heavy metals indicated all sites were unpolluted to moderate pollution level, in comparison to circumstance in autumn, the ones in spring manifested a deeper pollution degree, particularly for Cr and As. Ecological risk indexes of heavy metals in sediments ranged from 225.86 to 734.20 in spring, from 196.69 to 567.52 in autumn, respectively, suggesting that most of sites were moderate ecological risk or considerable ecological risk, and a very few were high ecological risk. Moreover, ArcGIS10.2 software was used to visualize their spatial distribution, whose results showed the trend were similar from spring to autumn. The results of the Pearson correlation analysis and principal components analysis showed that Cu, Hg and Pb might be affected by anthropogenic activities, and As might come from natural source such as atmospheric inputs. The cluster analysis showed that heavy metals were mainly affected by negative feedback of human beings on the environment.